Peripheral sensory neuropathy is associated with circulating angiopoietins in type 2 diabetes patients in Ghana - Agyekum, J.A.; Yeboah, K. (Journal of Clinical & Translational Endocrinology, 2023)
Objective: Peripheral sensory neuropathy (PSN) is a common complication of type 2 diabetes (T2DM) that can lead to frequent ulcerations, lower extremities, and reduced quality of life. Imbalance in the circulating levels of angiogenic growth factors, notably, angiopoietin (Ang)-1, Ang-2 and vascular endothelial growth factor (VEGF) may be among the underlying mechanisms of PSN in T2DM patients. We studied the association between PSN and angiogenic growth factors, Ang-1, Ang-2 and VEGF in T2DM patients in Ghana. Methods: In a case-control study design, PSN was evaluated in 160 patients with T2DM and 108 nondiabetic controls using vibration perception threshold (VPT) and diabetic neurological examination (DNE). The definition of PSN was abnormal VPT (≥25 mV) or the presence of neuropathic symptoms on examination (DNE score > 3). In addition, fasting venous blood samples were collected to measure circulating levels of Ang-1, Ang-2 and VEGF. Results: Compared to non-diabetic controls, patients with T2DM had a higher prevalence of PSN using abnormal VPT (20.6 % vs 2.8 %, p < 0.001) or neuropathic symptoms (35.6 % vs 3.7 %, p < 0.001). Compared to nondiabetic controls, patients with T2DM had increased levels of Ang-2 [597 (274 – 1005) vs 838 (473 – 1241) ng/ml, p = 0.018] and VEGF [48.4 (17.4 – 110.1) vs 72.2 (28 – 201.8), p = 0.025] and decreased Ang-1 levels [41.1 (30 – 57.3) vs 36.1 (24.7 – 42.1) ng/ml, p = 0.01]. In regression analyses, an increase in Ang-1 levels was associated with decreased odds, while an increase in Ang-2 levels was associated with increased odds, of abnormal VPT and neuropathic symptoms in T2DM patients. Conclusion: In our study population, PSN was associated with reduced plasma levels of Ang-1 and increased plasma levels of Ang-2 in patients with T2DM. Therefore, an imbalance of angiopoietins may be associated with PSN in T2DM.
Research Article
Keywords: Angiopoietins; VEGF; Peripheral sensory neuropathy; Type 2 diabetes